Massive Fetomaternal Hemorrhage Caused by an Intraplacental Choriocarcinoma: A Case Report - Anna-Karina Aaris Henningsen; Lisa Leth Maroun; Hanne Havsteen; Jens Svare (Case Reports in Medicine)
Background. Intraplacental choriocarcinoma is a rare but highly malignant trophoblastic neoplasm. When found near term the risk of maternal metastasis is high because of the late diagnosis. Case. We describe a case of an intraplacental choriocarcinoma diagnosed postpartum after a near-term delivery of a severely anemic infant. A fetomaternal hemorrhage resulted in a hemoglobin concentration in the infant of only 2,1 g/dL. Neither mother nor child showed signs of metastatic disease. The macroscopic examination showed a hydropic placenta weighing more than 1 kilogram. Microscopy showed an intraplacental choriocarcinoma 3 cm in diameter. The tumor had infiltrated the maternal basal plate. Conclusion. Fetomaternal bleeding is a rare form of presentation of choriocarcinoma but its presence should always warrant detailed examination of placenta, mother, and infant.